On the Bootstrap of the Maximum Score Estimator - Abrevaya, Jason; Huang, Jian (Econometrica, 2005)
This paper shows that the bootstrap does not consistently estimate the asymptotic distribution of the maximum score estimator. The theory developed also applies to other estimators within a cube-root convergence class. For some single-parameter estimators in this class, the results suggest a simple method for inference based upon the bootstrap.